Analysis on Behavioral Intention Towards Music Streaming Service: A Case Study of Spotify Premium in Indonesia - Paula Kohar; Gracella Vernanda (iBuss Management, 2022)
The music industry is currently evolving as a result of the continuous advancement of digital technology. With a strong customer base mainly coming from millennial and Gen Z, Spotify is often considered to be the leading pioneer in music streaming service through the implementation of freemium business model. Although Spotify has dominated the music streaming market in the West, there is a much intense competition in the East – specifically in Indonesia – given the existence of other powerful players. Therefore, the researchers are eager to identify the factors influencing the intention to keep on using Spotify Premium among millennial and Gen Z users in Indonesia based on a “Unified Theory of Acceptance and Use of Technology 2 (UTAUT2)”. This research will be conducted through a quantitative approach using simple random sampling with the use of online questionnaire, and will be analyzed through “Partial Least Squares – Structural Equation Modeling (PLS-SEM)” with the help of SmartPLS software. A total of 100 valid responses are obtained from this research, showing that performance expectancy, effort expectancy, and habit significantly affects behavioral intention, whereas social influence, facilitating conditions, hedonic motivation, and price value do not.Keywords: UTAUT2, Behavioral intention, Music streaming service, Spotify Premium, Millennial, Gen Z, Indonesia